PENGELOMPOKAN MINAT BELAJAR MAHASISWA MENGGUNAKAN TEKNIK DATA MINING DENGAN METODE CLUSTERING - Andri, Andri; Marlindawati, Marlindawati (Universitas Bina Darma, 2015)
The development of information technology today allows data can be stored in digital form. At the college student population will continue to grow over time which causes the stored data, especially data related to students academic will continue to grow. Data mining is an activity that aims to explore the information from a pile of data. Data mining is the process of data analysis using software to find patterns or certain rules of a number of large amounts of data that is expected to find knowledge to support keputusan.Dalam this research will be mining the data related to the academic students to be able to know the learning interest of students there is in college. This study will produce a model that can be used for grouping students based on their learning interests. Data mining techniques used in this study is the clustering technique.